Factors Associated with Nurses' Motivation to Continuing Career Paths in Hospitals - Syaiful Bahrie; Rasmun; Abdul Kadir (PT FORMOSA CENDEKIA GLOBAL, 2023)
Nursing education as a mechanism for increasing the career path of nurses aims to produce nursing staff who master the science of nursing and are able to carry out nursing in a professional manner to the community. In continuing nursing education, one of the most important roles is motivation. This study aims to determine the factors related to the motivation of nurses to continue their career path at RSUD dr. Abdul Rivai Berau District. The research method used is a quantitative method with a cross-sectional research design. The sample in this study were all nurses with DIII degree in Nursing at RSUD dr. Abdul Rivai as many as 204 respondents